Analysis Of The Added Value Of Bawis Fish Chips Products In Poklahsar Saputra Snack City Bontang - Mandasari, Seski Kennata; Syafril, Muhammad; Saleha, Qoriah (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Bontang City, located in East Kalimantan Province, has a larger marine area than land area, offering significant potential in marine fisheries resources. One of the abundant yet undervalued marine commodities is bawis fish (Gerres sp.), which remains economically underutilized. This low economic value presents a challenge, particularly for coastal communities that depend on the fisheries sector for their livelihoods. Increasing the added value of bawis fish through processing into higher-value products is therefore essential. One such initiative is the production of bawis fish chips, developed by the Processing and Marketing Group (Poklahsar) Saputra Snack, led by a local entrepreneur in Bontang. This study aims to assess the economic value added from bawis fish chips using the Hayami value-added analysis method. The findings indicate that the product yields an added value of IDR 27,151 per kilogram, with a value-added ratio of 37%. This implies that for each kilogram of raw bawis fish processed, an additional economic value of IDR 27,151 is generated. Based on the Hayami criteria, this level of value addition is classified as moderate (15%–40%). The results suggest that processing bawis fish into chips has the potential to serve as an effective strategy for enhancing the economic well-being of small-scale fishery enterprises.